DETERMINANT OF CAPITAL STRUCTURE : COAL AND NON COAL MINING INDUSTRY ON THE INDONESIA STOCK EXCHANGE (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2021)
This research was conducted to analyze the effect of debt costs, dividend policy, profitability, company size, business risk, and company growth on the capital structure of coal and non-coal mining industry on the Indonesia Stock Exchange 2015-2019 period, and to analyze the differences in the effect sixth determinant of capital structureÂ in the two industrial subsectors studied. Based on purposive sampling method was obtained 19 coal mining companies and 17 non-coal mining companies as the research sample. The analytical method used is multiple linear regression analysis and Chow test. The analysis showed that simultaneously cost of debt, dividend policy, profitability, company size, business risk, and company growth has a significant effect on the capital structure of the coal sub-sector, but no significant effect on non-coal sub-sector. Partially, the sixth of these variables have varying effect in the two industrial subsectors studied. Chow test results indicate a difference in effect cost of debt, dividend policy, profitability, company size, business risk, and company growth on capital structure decisions in the coal and non-coal sub-sectors. The limitation of this research is only examines the stability of the parameters in the regression model without informing how big a change or difference. The results of this study are beneficial to mining companies and academics.